Design and Construction of a Web-Based Sales Information System (Case study of a simple coffee shop business) - Ariati, Mila; Rusnedy, Hidayati; Joko Musridho, Raja (Journal of Engineering Science and Technology Management (JES-TM), 2026)
Sales transactions at Kedai Kopi Sederhana are still carried out manually through handwritten order records, cash payments, and daily sales reports without digital support. This manual process leads to several issues, including recording errors, inaccurate orders, data loss risks, and delays in generating sales reports. This study aims to design and develop a web-based sales information system to improve operational efficiency and data accuracy. The FAST (Framework for the Application of Systems Thinking) method was used, consisting of scope definition, problem analysis, requirements analysis, logical and physical design, system construction, and testing. The system was developed using PHP with the Laravel framework and MySQL database. The results show that the system successfully automates ordering, payment validation, menu management, and real-time sales reporting. Black Box testing indicates that all features function properly according to user requirements. Therefore, the system enhances business efficiency, reduces recording errors, and enables the business owner to monitor sales performance more effectively.